Financial Performance Analysis Of The Balai Yasa Lahat Employees' Cooperative - Leny Veronika; Darwin Kesuma; Mujari Mujari (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
The purpose of this study is analyze the Financial Performance of the Balai Yasa Lahat Employee Cooperative in terms of the Financial Ratios of Liquidity, Solvency, and Profitability. The aim was to determine the financial position of the Balai Yasa Lahat Employee Cooperative. The research method used a quantitative descriptive approach in accordance with the standards of the Regulation of the Minister of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia Number: 22/PER/M.KUKM/IV/2007 concerning Guidelines for Cooperative Rating. The results of the study show that the analysis of the financial report performance of the Liquidity Ratio at the Balai Yasa Lahat Employee Cooperative from 2021 - 2023 shows a figure with the criteria of